2023
DOI: 10.28945/5070
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Perceived Organizational Support (POS) and Turnover Intention: The Mediating Role of Job Motivation, Affective and Normative Commitment

Abstract: Aim/Purpose: The study aims to examine the mediating role of job motivation and affective and normative commitment on the relationship between perceived organizational support (POS) and job turnover intention. Background: POS refers to employees’ beliefs and perceptions concerning the extent to which the organization values their contributions, cares about their well-being, and fulfils their socio-emotional needs. To date, research has shown that employee turnover is a complex construct resulting from the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…According to research by (Akgunduz & Sanli, 2017;Hashish, 2015;Jolly et al, 2021;Liu et al, 2018;Sartori, 2023) there is a negative correlation between organizational support and work intention. The results showed that the higher the level of support felt by an organization's employees, the lower the likelihood that they would want to leave their jobs.…”
Section: Organizational Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research by (Akgunduz & Sanli, 2017;Hashish, 2015;Jolly et al, 2021;Liu et al, 2018;Sartori, 2023) there is a negative correlation between organizational support and work intention. The results showed that the higher the level of support felt by an organization's employees, the lower the likelihood that they would want to leave their jobs.…”
Section: Organizational Supportmentioning
confidence: 99%
“…High employee turnover rates in the banking sector can hurt company performance and the stability of the financial industry as a whole. Previous research on Emotional Intelligence in Organizational Support shows positive results (Fazio, 2017;Mahon et al, 2014;Wen et al, 2019) Previous research on Organizational support for Turnover Intentions showed negative results (Jolly et al, 2021;Sartori, 2023). Previous research related to Organizational support for career adaptability showed positive results (Agoes Salim et al, 2023;Guan et al, 2016;Ocampo et al, 2018;Sunarjo et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…The initial paper (Sartori et al, 2023) addresses the phenomenon of employee resignation and adopts an applied psychology lens to empirically understand the role of organizations in reducing employee turnover intention. The article makes a compelling case to show how the traditional lens of work and organizational psychology can be extended to a macro-social approach.…”
Section: The Seriesmentioning
confidence: 99%
“…Similarly, when organizations provide robust support for safety, employees experience increased job satisfaction, reduced stress levels, and enhanced overall well-being (Bunner et al, 2021;. Moreover, a recent study (Sartori et al, 2023) underlined that the perception of organizational support plays a key role in reducing turnover intention, creating a sense of obligation to return the favor, and leading to high commitment. Therefore, this study aims to examine the role of these two factors in employee performance and well-being, considering the psychological aspects associated with workplace safety.…”
Section: Introductionmentioning
confidence: 99%
“…First, we aim to explore the mediating role of safety climate in the relationship between Perceived Organizational Support for Safety (POSS) and employee well-being. In fact, while some studies have previously explored the impact of perceived organizational support on job performance and wellbeing (Sartori et al, 2023), the role of safety climate as the mediator in this context remains underexplored. Understanding how organizational support is related to safety climate, and subsequently, to well-being, can provide practical insights for organizations to create a more supportive and safe work environment.…”
Section: Introductionmentioning
confidence: 99%